Wilhelm Dilthey's hermeneutics and its relevance to Islamic studies - Murdiati, Dwi; Mukalam, Mukalam (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2023)
This study aimed to describe William Dilthey's hermeneutics and show its relevance to the study of Islamic history. This research is interesting to do when looking at the relationship between hermeneutics and Islamic studies, in the mainstream, it is in normative Islamic studies.  This study used descriptive analytical methods to describe the ins and outs of Dilthey's hermeneutics and the relevance of this hermeneutic in Islamic studies. The results showed that historical Islamic studies can utilize three elements in Dilthey's hermeneutics, namely Erlebnis (world of inner experience), Ausdruck (expression of life) and Verstehen (understanding). In addition, historical Islamic studies can also take advantages of the three conditions in Dilthey's hermeneutics, namely descriptive psychology, hermeneutical circles and socio-cultural knowledge.